MOTOR NEURON DISEASE: A CASE OF MISGUIDED THERAPEUTIC NIHILISM. Issue 11 (14th October 2015) - Rossor, Alexander; Josifova, Dragana; Howard, Robin; IsaacsItua, Alifa
Abstract : We report the case of a 62 year old gentleman with sensorineuronal hearing loss beginning in the second decade. At the age of 40 he collapsed and was unable to walk more than a few metres. He was admitted to hospital and diagnosed with a motor neuron disease on the basis of an EMG. Examination at the time revealed bilateral deafness, facial weakness, dysphagia, dysphonia and both proximal and distal weakness. The family history was remarkable for two sisters who died of a similar condition in the second decade. In view of the combination of sensory neuronal deafness and a motor neuronopathy, a diagnosis of Brown Violetta Van Laera (BVVL) syndrome was made. A PEG tube was inserted and the patient was discharged to a nursing home for palliation. After several months, our patient discharged himself, reintroduced thickened fluids resulting in removal of the PEG tube. His clinical condition has continued to improve although he intermittently requires a wheelchair. Genetic testing of the SLC52A3 gene revealed two missense mutations (p.Glu36Lys and p.Val413Ala) confirming the clinical diagnosis of BVVL. SLC52A3 encodes a riboflavin transporter and in case series, riboflavin supplementation has halted or reversed the disease.